(untitled) (Journal of Technology and Operations Management, 2015)
Job turnover is traditionally faced by organizations in many industries. Implications such as resources wastage and low productivity can be derived from turnover issue. Turnover intention was found to be a reliable predictor for actual turnover in previous studies. Consequently, this demands some insights on turnover intention issue especially within Malaysian context. This paper will focus on determining the relationship of job characteristics on turnover intention among manufacturing operators particularly in Electrical and Electronics sub-sector. The study was conducted amongst the operators of manufacturing industry in Peninsular Malaysia (N=800). Considering that Malaysia manufacturing industry has shown a strong economic growth through large investment in economic activities, it is important for all manufacturing companies to retain talented employees and reduce turnover problem in order to be more productive and competitive. The findings had accepted the research hypothesis. Dimensions of job characteristics (i.e. skill variety, task identity and feedback) had significantly correlated and contributed to the turnover intention. The findings had contributed to the theoretical significance through the examination of direct relationships between job characteristics on turnover intention among local operators in manufacturing sector based on the high turnover rate in Malaysia manufacturing sector between the years 2008 until early of 2011.